Energy-Efficient IP Core Network Configuration Under General Traffic Demands - Zhi Zhang; Bejerano, Yigal; Antonakopoulos, Spyridon (IEEE/ACM transactions on networking, 2016)
We consider the problem of minimizing the power consumption of IP core networks by means of power aware configuration of the Points of Presence (PoPs), given general traffic demands on the links. Although the problem is in general NP-complete, we give an optimal algorithm for an important variant where the number of ports on each line-card chassis is 2. For the general problem, we design two approximation algorithms with respective P/2 and 2lnN approximation ratios, where P is the number of ports on each line-card chassis, and N is the number of chassis within the PoP. When the traffic demands are correlated, we prove that our algorithms are optimal. Extensive simulations demonstrate that our PoP configuration algorithms significantly outperform existing design solutions over a wide range of traffic instances.